THE EFFECT OF INFORMATION GAP TECHNIQUE AND ACHIEVEMENT MOTIVATION TOWARD STUDENTSâ SPEAKING ABILITY (An Experimental Study of the Tenth Grade Students of MAN SELONG) - M, Asrobi,; K, SEKEN,; W, SUARNAJAYA, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study aims at investigating the effect of information gap technique and achievement motivation toward the speaking ability of the tenth grade students of MAN Selong. Designed as an experimental study, it examined a sample of two classes of grade ten students of MAN Selong. Cluster random sampling technique was used to take the sample. The data were collected through a speaking test and questionnaire of achievement motivation and analyzed by using two way ANOVA analysis and Tuckey test. Then, the findings can be stated as follows: (1) information gap technique is more effective than conventional technique in teaching speaking; (2) there is interaction effect of teaching techniques and achievement motivation toward studentsâ speaking ability; (3) there is a significant difference of speaking ability between high achievement motivation students who were taught using information gap technique and high achievement motivation students who were taught using conventional technique; (4) there is no significant difference of speaking ability between low achievement motivation students who were taught conventional technique and low achievement motivation students who were taught using information gap technique. In general, information gap technique is more effective than conventional technique for teaching speaking either for high achievement motivation students or for those with low achievement motivation students. Â Key words: Information Gap, Achievement Motivation, and Speaking Ability